The association between dietary pattern and depression in middle-aged Korean adults - Park, Seon-Joo (Nutr Res Pract, 2019)
BACKGROUND/OBJECTIVES: The association between dietary patterns and depression has been reported but the results have been inconsistent. This study was conducted to investigate the association between dietary patterns and depression in middle-aged Korean adults. SUBJECTS/METHODS: The participants were selected from a community-based cohort, a subset of the Korean Genome and Epidemiology Study. Depression was assessed using the Korean version of the Beck Depression Inventory (BDI) and those with a BDI score ≥ 16 were defined as having depression. The subjects' food intakes over the year preceding the survey were estimated by using a validated semi-quantitative food frequency questionnaire. Dietary patterns were identified by using factor analysis. Multiple logistic regression was used to assess the association of dietary pattern with depression. RESULTS: Among 3,388 participants, 448 (13.2%) were identified as having depression. We identified two major dietary patterns: ‘Healthy’ dietary pattern was characterized by high intakes of vegetables, soybeans, mushroom, seaweeds, white fish, shellfish and fruits and a low intake of white rice. ‘Unhealthy’ dietary pattern was characterized by high intakes of white rice, meats, ramen, noodles, bread and coffee and a low intake of rice with other grains. Compared with subjects in the lowest quartiles, those in the highest quartiles of the healthy dietary pattern had a significantly lower odds ratio (OR = 0.59, 95% CI: 0.42–0.82, P for trend = 0.0037) after adjusting for potential confounders. In contrast, the unhealthy dietary pattern was negatively associated with depression (OR = 1.65, 95% CI: 1.19–2.28, P for trend = 0.0021). CONCLUSION: This results suggest that a healthy dietary pattern (rich in vegetables, soybeans, mushroom, seaweeds, white fish, shellfish, and fruits) is associated with low risk of depression. Whereas an unhealthy dietary pattern (rich in white rice, meats, ramen, noodles, bread, and coffee) is associated with a high risk of depression in middle-aged Korean adults.